Perception et représentation - De quelques structures infinitives et participiales en look, see, listen et hear - Éric Gilbert (Anglophonia)
This paper deals with a special use of the verbs of perception look, see, listen and hear within infinitive clauses such as To look at her you’d think she was an angel. These verbs of perception entail the attribution of a property to the perceived object, which, in this kind of use, differs from its real properties and thus establishes a qualitative alterity endowing these structures with a counterfactual value. A similar phenomenon can be found with participial clauses such as Looking at him, one would never know he had been so ill. The present study seeks to describe the mechanism underlying the appearance of this value using the metalinguistic tools of the Theory of Enunciative Operations developed by A. Culioli. This phenomenon is indeed the result of a combination of operations that the TOE, as a model of the construction of meaning, seems particularly suited to represent.